Prefaces and Postscripts in Juejiao tongwen ji: An Encounter of Ming Literati and Christian Doctrines - Xie, Jingzhen (Transformation, 2026)
This article discusses Ming literati's reception of Western learning by analysing prefaces and postscripts composed for Jesuit publications before 1615, which were collected in the Juejiao tongwen ji ????? (?learning from a distant land common to cultures?, JJTWJ, 1615). It first examines these texts and their authors, then explores how the missionaries? character traits convinced literati of the unity of knowledge and action. Late Ming literati recognized the strong moral foundation of Catholic values in pursuing shixue (practical learning), while also promoting the theory that Western learning originated within Chinese scholarship. Third, it considers literati attitudes ? ranging from admiration to scepticism ? revealing nuanced positions shaped by cultural and intellectual exchange. These perspectives highlight a dynamic interplay of governance, faith, and reason in the East?West encounter. Later Qing debates, including the Rites Controversy, underscore the legacy of the JJTWJ and affirm the historical significance of this study.